1967
DOI: 10.1002/jlac.19677020111
|View full text |Cite
|
Sign up to set email alerts
|

Umsetzung von Natrium‐p‐toluolsulfinat mit organischen Halogeniden

Abstract: Das Sulfinat-Atanion haltsich streng an die allgemeinen Substitutionsregeln, die fur ambifunktionelle Anionen gefordert werden. Organische Halogenide rnit mehr oder weniger polarer Kohlenstoff-Halogen-Bindung reagieren rnit Natrium-p-toluolsulfinat nach sN2 unter Bildung von Sulfonen. Halogenide, die leicht eine Elektronenlucke in Form eines Carbenium-Ions zu bilden vermogen, reagieren nach s N 1 unter Bildung von Sulfinsaure-Derivaten, die normalerweise instabil sind und weiterzerfallen. Die bisher unbekannte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
3

Year Published

1968
1968
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 15 publications
(1 reference statement)
1
4
0
3
Order By: Relevance
“…Reaction of sulfinic acid salts with chloromethyl methyl ether (159). [146] Although the preferred or exclusive O attack by the in situ generated methyldiazonium ion ( Table 7, entry 1), dimethyl sulfate (entries 3 and 5), and methyl tosylate (entries 4 and 6) on the one hand and the preferred S attack by methyl iodide (entries 7 and 8) on the other might be explained by the HSAB principle, it should be noted that the silver salt of p-toluenesulfinic acid also reacts with methyl iodide at the sulfur atom with high selectivity (Table 7, entry 9). Attack at the oxygen atom of the sulfinate anions has also been observed in their reactions with triethyloxonium tetrafluoroborate, [155] acetyl chloride, [146] or ethyl chloroformiate.…”
Section: Enolate Anionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reaction of sulfinic acid salts with chloromethyl methyl ether (159). [146] Although the preferred or exclusive O attack by the in situ generated methyldiazonium ion ( Table 7, entry 1), dimethyl sulfate (entries 3 and 5), and methyl tosylate (entries 4 and 6) on the one hand and the preferred S attack by methyl iodide (entries 7 and 8) on the other might be explained by the HSAB principle, it should be noted that the silver salt of p-toluenesulfinic acid also reacts with methyl iodide at the sulfur atom with high selectivity (Table 7, entry 9). Attack at the oxygen atom of the sulfinate anions has also been observed in their reactions with triethyloxonium tetrafluoroborate, [155] acetyl chloride, [146] or ethyl chloroformiate.…”
Section: Enolate Anionsmentioning
confidence: 99%
“…[145] In an extensive study, Schank showed that primary and secondary alkyl halides, a-halocarbonyl compounds, as well as ahaloethers exclusively attack at the sulfur atom of ptoluenesulfinate anions (Scheme 72). [146] Lindberg derived exclusive S attack from the kinetics of the reactions of m-and p-substituted sodium arenesulfinates with bromoacetate and bromoacetamide in water. [147] Other displacement reactions at saturated carbon atoms, for example, epoxides [148] or b-propiolactones, [149] and nucleophilic aromatic substitutions of p-nitrochlorobenzene also proceed at sulfur to give sulfones exclusively.…”
Section: Enolate Anionsmentioning
confidence: 99%
“…[145] In einer ausführlichen Studie zeigte Schank, dass primäre und sekundäre Alkylhalogenide, a-Halogencarbonylverbindungen sowie a-Halogenether ausschließlich am Schwefelatom von p-Toluolsulfinat-Ionen angreifen (Schema 72). [146] Lindberg leitete den ausschließlichen S-Angriff aus der Kinetik der Reaktionen von m-und p-substituierten Natriumarensulfinaten mit Bromacetat und Bromacetamid in Wasser ab. [147] Andere Substitutionen an gesättigten Kohlenstoffatomen, zum Beispiel bei Epoxiden [148] oder b-Propiolactonen, [149] und nucleophile aromatische Substitutionen an p-Nitrochlorbenzol verliefen ebenfalls am Schwefelatom unter ausschließli-cher Sulfonbildung.…”
Section: Angewandte Chemieunclassified
“…9 in Tabelle 7). Angriff am Sauerstoffatom der Sulfinat-Ionen wurde auch bei ihren Reaktionen mit Triethyloxonium-tetrafluoroborat, [155] Acetylchlorid [146] oder Chlorameisensäu-reethylester [144c] beobachtet. Lassen sich diese Befunde auch auf der Basis von Schema 2 deuten?…”
Section: Angewandte Chemieunclassified
See 1 more Smart Citation